Deterioration and shelf-life extension of fish and fishery products by modified atmosphere packaging - Payap Masniyom (Songklanakarin Journal of Science and Technology (SJST), 2011)
Fish and fishery products have been recognized as a nutrition source due to their high protein content. Moreover, theycontain considerable amount of unsaturated fatty acids, especially omega-3 fatty acids, which are regarded as preventivecompounds. However, shelf-life of seafood is limited by biochemical and microbiological changes. Modified atmospherepackaging (MAP) is widely used for minimally processed fishery products including fresh meat for retarding microbial growthand enzymatic spoilage. CO2, O2, and N2 are most often used in MAP. CO2 enriched atmosphere inhibits the autolyticdegradation of fish muscle during storage. However, high levels of CO2 negatively affect product quality, especially by increasingdrip loss and altering texture. Development of satisfactory methods for shelf-life extension that ensure qualitymaintenance of products with minimum loss has drawn the attention of food technologists. The application of MAP andcombination process in seafood is a promising preservation method to extend the shelf-life of fish and fishery products.